2021
DOI: 10.3389/fpubh.2021.766146
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist's Perspectives on Administering a COVID-19 Vaccine in Community Pharmacies in Four Balkan Countries

Abstract: Community pharmacists expanded their roles and engaged in vaccination services in many countries around the world, but not in Balkan countries. This research aimed to assess the perceptions of pharmacists on involvement in the coronavirus disease (COVID-19) vaccine administration in four Balkan countries (Albania, Bulgaria, Romania, and Serbia). A cross-sectional survey was conducted using an online questionnaire that was distributed to community pharmacists across these countries between February and March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Although the effect of pandemic-related stressors on the mental well-being and burnout of nurses and physicians is well documented, [7][8][9][10] less is known about pharmacists' perceptions of their roles during the COVID-19 pandemic and more specifically how vaccinations have contributed to burnout experienced within the profession during the pandemic thus far. [11][12][13][14] The aim of this qualitative study was to explore the perceptions of pharmacists about their vaccinator role during the COVID-19 pandemic. This study is part of a series included in this supplement to the Canadian Pharmacists Journal that together summarize the findings of a program of research funded by the Public Health Agency of Canada, examining community pharmacy vaccination services and integrating a vaccination delivery framework (Comfort Ask Relax Distract; CARD) to improve the experiences of vaccine clients and pharmacy staff.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of pandemic-related stressors on the mental well-being and burnout of nurses and physicians is well documented, [7][8][9][10] less is known about pharmacists' perceptions of their roles during the COVID-19 pandemic and more specifically how vaccinations have contributed to burnout experienced within the profession during the pandemic thus far. [11][12][13][14] The aim of this qualitative study was to explore the perceptions of pharmacists about their vaccinator role during the COVID-19 pandemic. This study is part of a series included in this supplement to the Canadian Pharmacists Journal that together summarize the findings of a program of research funded by the Public Health Agency of Canada, examining community pharmacy vaccination services and integrating a vaccination delivery framework (Comfort Ask Relax Distract; CARD) to improve the experiences of vaccine clients and pharmacy staff.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these studies had limitations including small sample size and lack of theoretical frameworks to drive the research. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed pharmacists' experiences, practices and attitudes towards vaccination around the globe. However, many of these studies had limitations including small sample size and lack of theoretical frameworks to drive the research 19–26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey found that pharmacies are regarded as ideal vaccination settings by the population [8] . However, by spring 2021 only few jurisdictions in Europe permitted pharmacists to conduct COVID-19 vaccinations [1] , [9] , [10] , [11] , [12] . Moreover, there is a sometimes shameful controversy among healthcare providers on who is eligible to provide vaccinations and who is not, instead of reaching out for higher vaccination rates [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%